2011
DOI: 10.1111/j.1468-1331.2010.03336.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thrombin-antithrombin complex contents in plasma and hematoma fluid of hypertensive intracerebral hemorrhage patients after clot removal

Abstract: This study indicates that TAT complex levels of plasma and hematoma fluid correlate positively with the severity of ICH. Determination of the plasma TAT complex concentration is helpful for the evaluation of the severity of post-ICH brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…TAT complex concentrations in plasma samples were determined at Shanghai Institute of Immunology, China, using commercially available Assay Max Human TAT Complex enzyme-linked immunosorbent assay (ELISA) kit (ASSAYPRO, St. Charles, MO) as previously described. [21]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TAT complex concentrations in plasma samples were determined at Shanghai Institute of Immunology, China, using commercially available Assay Max Human TAT Complex enzyme-linked immunosorbent assay (ELISA) kit (ASSAYPRO, St. Charles, MO) as previously described. [21]…”
Section: Methodsmentioning
confidence: 99%
“…[68] Delayed secondary brain injury may be caused by decreased local blood flow, [912] inflammation, [1316] peripheral edema, [17,18] degradation products of hemoglobin, [19,20] matrix metalloproteinase, and thrombin. [21–23] Neuronal apoptosis is common after ICH. [13,24] Although much effort has been made to understand the pathogenesis of ICH, no effective medical or surgical therapy has been firmly established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed argatroban treatment reduced oedema in a rat model of ICH, and did not increase collagenase‐induced haematoma volume when given into the clot after 3 h or given systemically at 6 h , which indicated that the time‐window for administration of argatroban is extremely important. In patients, thrombin–anti‐thrombin complex (TAT) levels of plasma and haematoma fluid correlate positively with the National Institutes of Health stroke scale and the severity of ICH . As opposed to conventional therapeutic approaches, the administration of argatroban could effectively limit oedema formation and neuronal damage, improving survival and functional outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the most active field was that of stroke pathophysiology, treatment and outcomes . The role of genetics in pre‐disposition towards stroke attracts much attention, and there are several complex genetic traits with differences between ethnic groups.…”
mentioning
confidence: 99%